Characterization of alternative splicing mechanisms of SRRM2 splicing factor in human immune cells - Gason, Isaac Reuben (2019)
Alternative splicing, which is vital for the immune system’s proper functioning, is influenced by cis-acting elements and trans-acting splicing factors. Previously, we discovered that monocytic differentiation to macrophages resulted in decreased expression of the splicing factor, the serine/ arginine repetitive matrix protein 2 (SRRM2). We predict that SRRM2 plays an important role in monocytic differentiation. To understand the function of SRRM2, we cloned minigenes of proline rich 14 and SH3-domain binding protein 2 (MiniSH3BP2) which are predicted targets of SRRM2. We tested if these minigenes responded similarly as their endogenous counterparts by knocking down SRRM2. MiniSH3BP2 responded to the knockdown similarly by demonstrating a greater increase in exon skipping. Next, we attempted to discover the SRRM2 responsive element. A region along the first intron of MiniSH3BP2, which was predicted computationally to be a possible responsive site, was mutated. Unlike MiniSH3BP2-wildtype, we observed no drastic increase in the percentage of MiniSH3BP2-mutant exon skipping for SRRM2 knockdown samples. This observation could be implicated by the presence of two new unknown bands. However, when we compared the scrambled control with SRRM2 knockdown samples, no drastic change in MiniSH3BP2-mutant exon skipping was observed suggesting that this motif might be the responsive element.